ANALISIS MOTIVASI INTERNAL DAN EKSTERNAL PENYULUH PERTANIAN DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Supiyani Wati; Rosnita '; Roza Yulida (Indonesian Journal of Agricultural Economics, 2015)
This research aims to analyzed the extention of counseling and analyzed of the factors of motivation internal and external of agricultural extension officer, in the district of Gunung Toar Regency Kuantan Singingi. Research using survey method was carriate out from November fill April 2015 in sub Gunung Toar district Kuantan Singingi with the largest amounted of rubber farmers and a rubber plant large a mount in Riau Province. Sampling is caried out againts census 5 extension officers in the UPTD plantation sub Gunung Toar. Execution of counseling in analistis are descriptive and extension officers motivation with scale likert. The motivational variable refers to the theory of extension officers in Kadarisman Saydam (2012), with respect to internal and external factors. Research results show that the extention of counseling in the sub Gunung Toar was alreadygood, where the extension officers LAKU system using the methods with the extension in the form of print, extension officers amountedto 5 people with education level of 60 percent SMA/SMK/equal and 40 percent of the graduates, number of villages built average 2-4 village per extension officers. The motivation extension officers was enough high score average (2,97), where internal motivation variables already on the category is Quite high with the score average (3,33) while the external motivation also on categories is Quite high with the score average (2,61).